Pengaruh Pembiayaan Mudharabah Dan Pembiayaan Musyarakah Terhadap Return Of Asset (Roa) Pada Bank Syariah Mandiri - Dewi, Ratih Komala (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
Â The study aims to determine the effect of Mudharabah Financing and Musyarakah Financing on Return of Assets (RoA) in Bank Mandiri Syariah in 2014-2018. The method of data collection in the subject of research was obtained by tabulating secondary data in the form of financial statements at Bank Mandiri Syariah in 2014 - 2018. The quantitative method of data analysis was done by processing SPSS software data in the form of classic assumption testing, testing F test statistics and testing t test to draw interesting conclusion. The results of this study indicate Mudharabah Financing and Musyarakah Financing have a positive influence on Return of Assets (RoA) in Bank Mandiri Syariah in 2014-2018 both partially and simultaneously.